629 Improving Gentamicin Prescribing for Intra-Abdominal Sepsis on a General Surgical Firm. (19th August 2022) - Fardanesh, A; Koo, HF; Van den Berghe, C; Gathercole, G; Dilke, S; Sengupta, N
Abstract: Aim: Gentamicin is recommended by local guidelines for the empirical treatment of intra-abdominal sepsis. However, severe side effects that can occur through prolonged raised through levels requires its use through a specific dosing protocol. Challenges of this means it often "falls off" the drug chart, leading to suboptimal drug-levels. The aim of this quality improvement project was to improve the process of gentamicin prescription. Method: A two-week retrospective analysis of all patients admitted was performed to obtain baseline data. Information was collected on gentamicin use, if levels were taken at 6–14 hours post-dose, and if subsequently correctly re-prescribed. PDSA 1 involved placing posters in the surgical office, reminding the clerking doctor of the gentamicin protocol. PDSA 2 involved a departmental teaching session to reiterate the above intervention. Results: At baseline, only 7% (1/15) of patients prescribed gentamicin had a correct post-dose level taken and subsequently received a correct second dose. After PDSA 1, this rose to 67% (2/3). After PDSA 2, this level was similar at 60% (3/5). Furthermore, at baseline 47% (15/32) of patients deemed to have intra-abdominal sepsis received gentamicin. After PDSA 1, this proportion fell to 11% (3/28) and after PDSA 2 this was 38% (5/13). Conclusions: Education sessions and posters were effective at increasing the proportion of patients that received a safely prescribed second dose of gentamicin, as a result of correctly taken trough levels. However, a reduction in the percentage of patients receiving gentamicin for intra-abdominal sepsis possibly suggests further education on the role of gentamicin is required.